The EU’s Post-Lisbon Democratic Development: What Lessons for Iceland? - Conrad, Maximilian (Stjórnsýslustofnun, 2014)
Apart from the question of whether permanent exemptions from EU rules could be achieved in Iceland’s (by now halted) EU accession negotiations, the EU’s institutional development in the wake of the Lisbon Treaty has been used as a key argument for the conservative government to first suspend the negotiations and subsequently also to propose to withdraw the membership application altogether. In this regard, concerns about the democratic quality of EU decision making play a key role. However, as this article argues, the institutional development of the EU since Lisbon, particularly in relation to democratic governance, has been considerably more subtle than it is claimed to be and has to be seen as a continuation of a much longer process. More importantly, however, the debate leaves pressing questions about the nature of the EU as a polity unaddressed. In this context, this article addresses the question of what kind of democracy is possible in the kind of polity sui generis that the EU undoubtedly is.